Genome-wide linkage analysis of electrocardiographic and echocardiographic left ventricular hypertrophy in families with hypertension. - Mayosi, B; Avery, P; Farrall, M; Keavney, B; Watkins, H (2008)
AIMS: To localize chromosomal regions (or quantitative trait loci) that harbour genetic variants influencing the variability of electrocardiographic (ECG) and echocardiographic left ventricular hypertrophy (LVH). METHODS AND RESULTS: We evaluated genetic linkage to ECG Sokolow-Lyon voltage, ECG Cornell voltage product, ECG left ventricular (LV) mass, and to echocardiographic septal wall thickness, LV cavity size, and LV mass in 868 members of 224 white British families. A genome-wide scan was performed with microsatellite markers that covered the genome at 10-cM intervals and linkage was assessed by variance components analysis. We identified chromosomal regions suggestive of linkage for Sokolow-Lyon voltage on chromosome 10q23.1 [log(10) of the odds (LOD = 2.21, P = 0.0007)], for ECG Cornell voltage product on chromosome 17p13.3 (LOD = 2.67; P = 0.0002), and for ECG LV mass on chromosome 12q14.1 (LOD = 2.19; P = 0.0007). There was a single region of possible linkage for echocardiographic LV mass on chromosome 5p14.1 (LOD = 1.6; P = 0.003). CONCLUSION: Stronger genetic signals for LVH were found using electrocardiographic than echocardiographic measurements, and the genetic determinants of each of these appear to be distinct. Chromosomes 10, 12, and 17 are likely to harbour genetic loci that exert a major influence on electrocardiographic LVH.